INFLATSIYA INDEKSINING INVESTITSIYALAR SAMARADORLIGIGA TASIRI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the impact of the inflation index on the effectiveness of investments. It highlights the role of inflation in investment decision-making, the change in capital value, and its effect on real profitability indicators. The paper also examines methods for evaluating investments under inflationary conditions and identifies the risks faced by investors, along with measures to mitigate them.